Memórias da prostituição: território, poder e resistências em São Sebastião. Serra-ES (1960-1980) - Morgante, Mirela Marin (2020)
In the late 1960s, in the midst of the demographic and urban growth of Vitória, capital of Espírito Santo, the state government started to give speeches and implement practices of social ordering and hygiene in the city, which saw prostitution as a "socia